2009
DOI: 10.1016/j.ejcts.2008.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Stentless porcine valves in the right ventricular outflow tract: improved durability?☆

Abstract: Stentless porcine valves function well in the pulmonary position over the intermediate-term and are associated with low rates of reintervention in patients requiring a >19 mm valve or valved conduit. Longer-term follow-up and comparison with other alternatives will be necessary to determine if these valves are superior to commonly used allograft or bovine jugular venous valved conduits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…This is lower than what was observed by Dunne and colleagues, who reported pulmonary insufficiency in 12.5% of cases of structural valve dysfunction and mixed stenosis and insufficiency in an additional 16.7%. Hawkins et al reported low reintervention rate at five years (4/150 patients, 2.6%) for a similar aortic root bioprosthesis and all were due to stenosis. Of their remaining patients at five‐year follow‐up, only five patients had moderate insufficiency with the remainder having none to mild insufficiency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is lower than what was observed by Dunne and colleagues, who reported pulmonary insufficiency in 12.5% of cases of structural valve dysfunction and mixed stenosis and insufficiency in an additional 16.7%. Hawkins et al reported low reintervention rate at five years (4/150 patients, 2.6%) for a similar aortic root bioprosthesis and all were due to stenosis. Of their remaining patients at five‐year follow‐up, only five patients had moderate insufficiency with the remainder having none to mild insufficiency.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, this is the largest cohort of primarily pediatric patients undergoing RVOTR using the Freestyle porcine aortic root heterograft and our findings demonstrate good outcomes. Previous studies have demonstrated that porcine aortic valves in the non‐Ross population perform well in the short term and intermediate term . Dunne and colleagues reported their experience with 114 patients with a median age of 21 years.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although PVR in repaired TOF represents in adults a frequent surgical procedure of the RVOT, surgical management of an associated tricuspid regurgitation (TR), which is observed in up to 30% of patients, remains debated. [2][3][4] Indeed, only scarce data on the surgical management of TR at the time of PVR have been published so far, with controversial results. [5][6][7][8] In these adult patients with repaired TOF who underwent PVR, we sought to (1) determine factors that predispose to the development of significant preoperative TR and (2) evaluate the efficacy of a concomitant tricuspid valve (TV) repair at the time of PVR.…”
Section: See Editorial Commentary Page 224mentioning
confidence: 99%
“…Most patients receive a bio-prosthesis such as a homograft or heterograft, either stented or un-stented. [10][11][12] All of these valves are non-living and non-repairable, and share a common durability issue. They undergo a biodegenerative process and ultimately will fail with obstruction and/or insufficiency over time.…”
Section: T He Need For Pulmonary Valve Replacementmentioning
confidence: 99%